Beta-lactam antibiotic resistance among Escherichia coli isolates from patients with urinary tract infections in Vietnam: A systematic review and meta-analysis - Dat T Nguyen (Asian Pacific Journal of Tropical Medicine, 2024)
Objective: To investigate the evolving patterns of antimicrobial resistance against beta-lactam antibiotics in Escherichia coli isolates from urinary tract infection patients in Vietnam, covering the period from 2005 to 2022. Methods: 29 Descriptive studies published between 2010 and 2022 in English and Vietnamese were included in the analysis. Data on resistance rates to beta-lactam antibiotics, including cephalosporins and carbapenems, were extracted and analyzed. Weighted pooled resistance rates were calculated using random-effects models. Annual trends in resistance were assessed using linear regression analysis. Results: Among the beta-lactam antibiotics studied, Escherichia coli exhibited varying levels of resistance, with cephalosporins showing higher resistance rates compared to carbapenems. Weighted pooled resistance rates were 66% for cefotaxime, 65% for ceftriaxone, 54% for ceftazidime, and 56% for cefepime. In contrast, carbapenems demonstrated lower resistance rates, with weighted pooled resistance rates ranging from 3% to 4% for meropenem, ertapenem, and imipenem. Resistance rates were also observed for amoxicillin/clavulanate (35%), ticarcillin/clavulanate (26%), and piperacillin/tazobactam (12%). Significant annual increases in resistance were noted for imipenem (0.56%, P<0.001). Conclusions: This study highlights the critical issue of antimicrobial resistance in urinary tract infections in Vietnam and emphasizes the importance of prudent antibiotic use and the regular monitoring of resistance patterns. These insights are useful for guiding healthcare professionals in optimizing treatment strategies and for policymakers in formulating evidence-based clinical guidelines to combat antibiotic resistance effectively.